2010
DOI: 10.1021/pr1005873
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Definition of the Cell Wall of Mycobacterium tuberculosis

Abstract: The cell envelope of Mycobacterium tuberculosis (Mtb) is complex and diverse; composed of proteins intermingled in a matrix of peptidoglycan, mycolic acids, lipids, and carbohydrates. Proteomic studies of the Mtb cell wall have been limited; nonetheless, the characterization of resident and secreted proteins associated with the cell wall are critical to understanding bacterial survival and immune modulation in the host. In this study, the cell wall proteome was defined in order to better understand its unique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
57
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 59 publications
8
57
1
Order By: Relevance
“…A subsequent literature search revealed that almost all further selected IVE-TB proteins (14 of the 16) have been identified previously in M. tuberculosis proteomic studies, confirming the protein expression of the M. tuberculosis genes identified in our study (44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57) (Table III). Indeed, we observed that M. tuberculosis- FIGURE 3.…”
Section: Immunogenicity Of Newly Identified Ive-tb Agssupporting
confidence: 87%
“…A subsequent literature search revealed that almost all further selected IVE-TB proteins (14 of the 16) have been identified previously in M. tuberculosis proteomic studies, confirming the protein expression of the M. tuberculosis genes identified in our study (44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57) (Table III). Indeed, we observed that M. tuberculosis- FIGURE 3.…”
Section: Immunogenicity Of Newly Identified Ive-tb Agssupporting
confidence: 87%
“…The largest functional groups of proteins identified are predicted to be involved in cell wall processes, intermediary metabolism/respiration, or are conserved hypothetical proteins (47). This distribution of cell wall-associated proteins among functional groups is similar to what is seen in other M. tuberculosis cell wall proteome studies (48,49).…”
Section: Proteomic Analysis Of Differentially Abundant Proteins In Thsupporting
confidence: 70%
“…In humans, the OCTN1 transporter is required for ERG transport into cells and involves cotransport of Na ϩ (18). This leads us to speculate that the ERG transporter in mycobacteria may be a member of the monovalent cation:proton antiporter family or the H ϩ /Na ϩ -translocating F-type, V-type, and A-type ATPase superfamily, which both utilize Na ϩ as a substrate (41). Since ERG has anti-inflammatory properties (15), the secretion of this molecule by M. tuberculosis may play a role in modulating the immune response by the host during infection and therefore warrants further investigation.…”
Section: Role Of Ergothioneine In Mycobacteriamentioning
confidence: 99%